Comparison of clinical outcomes and safety of catheter ablation for atrial fibrillation supported by data from CT scan or three-dimensional rotational angiogram of left atrium and pulmonary veins - Lehar, František; Stárek, Zdeněk; Jež, Ondřej; Novák, Miroslav; Wolf, Jiří; Štěpánová, Radka; Kružliak, Peter; Kulík, Tomáš; Žbánková, Alena; Jančár, Radek; Vítovec, Jiří (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2015)
BACKGROUND: Catheter ablation in the left atrium has become a common therapeutic strategy in the management of atrial fibrillation (AF). The high degree of success and safety profile of this procedure is dependent on precise knowledge of the true anatomy in the chamber. This information is imported mostly from cardiac computed tomography. A novel method for imaging the left atrial anatomy is three-dimensional rotational angiography (3DRA). METHODS: The aim of our study was to the compare clinical outcome and safety of catheter ablation for atrial fibrillation guided by 3DRA vs. conventional CT scan. One hundred and twenty-five patients referred for AF catheter ablation at St. Anne's University Hospital Brno were included in the retrospective analysis of clinical outcome within the first year after the procedure. RESULTS: There was a close correlation in overall procedural parameters between the groups. The frequency of recurrent episodes of AF (24% in CT-guided group vs. 27% in 3DRA-guided group, P=0.721) as well as the onset of atypical atrial flutter after the procedure (10% vs. 8%, respectively, P=0.731) were similar in both groups. No difference in the number of patients necessitating repeat ablation (5% vs. 5%, P=0.984) was found. Procedural complications of ablations guided by 3DRA were comparable with those guided by CT (2% vs. 3%, respectively, P=0.568). CONCLUSION: 3DRA has proven to be a safe and simple method for imaging the left atrium and guiding catheter ablation for AF. This approach is anticipated to become a new standard in 3D reconstruction of the left atrium.
Keywords: recidiva; počítačová rentgenová tomografie; délka operace; Humans; lidé středního věku; venae pulmonales; Female; angiografie; výsledek terapie; lidé; Atrial Fibrillation; Radiography, Interventional; Heart Atria; katetrizační ablace; Operative Time; Angiography; ženské pohlaví; Male; Middle Aged; Tomography, X-Ray Computed; Pulmonary Veins; Treatment Outcome; srdeční síně; Recurrence; intervenční radiografie; mužské pohlaví; Catheter Ablation; fibrilace síní